From Power Politics to Conflict Resolution - Dunn, David J. author. aut Link
XII, 190 p.
Keywords: From Power Politics to Conflict Resolution surveys the development of the ideas of John W. Burton, an Australian civil servant and diplomat who became a prolific author in the fields of International Relations and Conflict Theory. This work, beginning with an introduction to his life and associations, assesses the development of Burton's ideas, at once critical of much of the conventional wisdom of International Relations as well as seeking to be innovative, helping us to understand the issues of peace and conflict in a changing world. A central theme is the development of a framework of ideas which Burton came to call provention .